Healthcare providers’ experiences of maternity care service delivery during the COVID-19 pandemic in the United Kingdom: a follow-up systematic review and qualitative evidence synthesis - Dasgupta, Tisha; Bousfield, Emily; Pathak, Yosha; Horgan, Gillian; Peterson, Lili; Mistry, Hiten D.; Wilson, Milly; Hill, Meg; Smith, Valerie; Boulding, Harriet; Sheen, Kayleigh S.; Van Citters, Aricca D.; et al. (Frontiers in Global Women's Health, 2024)
Problem and backgroundDuring the COVID-19 pandemic, there was substantial reconfiguration of maternity care services, affecting both users and healthcare providers (HCPs), in the United Kingdom (UK) and globally.AimTo further our understanding of the impact of maternity service reconfigurations in the UK, from the perspective of maternity HCPs.MethodsScopus, MEDLINE, EMBASE, CINAHL, PsycINFO and the Cochrane COVID Study Register were searched for relevant studies reporting qualitative data from the UK, published in English between 01 June 2021 and 30 September 2023. Qualitative data on HCPs’ experiences of maternity care reconfiguration during the pandemic were extracted from 15 studies. Data were subjected to thematic synthesis according to key service reconfigurations.ResultsNine themes were identified: Care-seeking and Care Experience: Changes to existing care, Limitations placed on the partner, Mental health and lack of support networks, and Barriers to successful implementation of reconfiguration strategies; Virtual Care: Impact on quality of care, Increased convenience and flexibility, and Digital exclusion; and Ethical Future of Maternity Care Services: Optimising patient care, and Service users and staff as the driving force for change. No studies reported on the concepts of Self-monitoring or COVID-19 vaccination.Discussion and conclusionThe review findings highlight HCPs’ views of the need for greater inclusion of partners, choice of virtual or in-person care for women and birthing people; and a need for co-designed services for future policy-making.